MUSYAWARAH SEBAGAI KARAKTER BANGSA INDONESIA - Teuku Ahmad Yani (Jurnal Community, 2016)
Deliberation is an invaluable heritage for the Indonesian citizen, by deliberation; it can give a harmony to the community. For an independent society harmonious relationship of mutual respect and respect the opinions of others is a positive side that is valuable. The discussion is not only a culture of preventive, but also happens when disputes. Keywords: deliberation, character of nation, harmony